2021
DOI: 10.1101/2021.02.19.21251501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disorganization of language and working memory systems in frontal versus temporal lobe epilepsy

Abstract: Cognitive impairment is a common comorbidity of epilepsy, and adversely impacts people with both frontal lobe epilepsy (FLE) and temporal lobe epilepsy (TLE). While the underlying neural substrates in TLE have been extensively investigated, functional imaging studies in FLE are scarce. In this study, we profiled cognitive dysfunction in FLE, and directly compared FLE and TLE patients to establish commonalities and differences. We investigated 172 adult participants (56 with FLE, 64 with TLE, and 52 controls), … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…Our study showed that working memory and language impairment in frontal lobe epilepsy was associated with reduced activation across attentional and executive systems, together with an attenuated deactivation of default mode regions, suggesting a reorganization of functional recruitment at the systems level. While atypical activation patterns were similar to those in TLE patients, reductions in default mode network deactivations appeared more marked in frontal lobe epilepsy patients, whereas those with TLE presented with less activations in posterior language areas during semantic tasks 101 . Collectively, these findings provide emerging evidence of both shared and syndrome specific impacts of different location-related epilepsies on brain functional networks.…”
Section: Extratemporal Lobe Epilepsy (Ete)mentioning
confidence: 50%
See 1 more Smart Citation
“…Our study showed that working memory and language impairment in frontal lobe epilepsy was associated with reduced activation across attentional and executive systems, together with an attenuated deactivation of default mode regions, suggesting a reorganization of functional recruitment at the systems level. While atypical activation patterns were similar to those in TLE patients, reductions in default mode network deactivations appeared more marked in frontal lobe epilepsy patients, whereas those with TLE presented with less activations in posterior language areas during semantic tasks 101 . Collectively, these findings provide emerging evidence of both shared and syndrome specific impacts of different location-related epilepsies on brain functional networks.…”
Section: Extratemporal Lobe Epilepsy (Ete)mentioning
confidence: 50%
“…In ETE (middle row), a study focusing on children with frontal lobe lesions demonstrated that despite the absence of significant differences in structural network parameters in patients, structural modularity increased with stronger cognitive impairment (middle left) 130 . Additionally, when comparing fMRI activation patterns in a verbal working memory task, frontal lobe epilepsy patients showed targeted reductions in the recruitment of specific networks, notably fronto-parietal and dorsal attention systems, while effects in TLE patients were more widespread (middle right) 101 . As for IGE (bottom row), a study in patients with juvenile myoclonic epilepsy and their unaffected siblings studied left hippocampal shape/positional anomalies, and found associations to atypical activation during a verbal memory task (bottom left)…”
Section: Figure 2 Prior Multimodal Imaging Studies On Connectome Markers Of Dysfunction In the Common Epilepsiesmentioning
confidence: 99%
“…49 Intrinsic connectivity gradients have recently been used to capture task-related functional reorganisation of episodic memory processes, as well as language and working memory systems in temporal lobe epilepsy. 50,51 To link our gradient findings of stronger differentiation between unimodal and transmodal systems in NDfE and PS to the histologically measured distribution of gene expression in the brain, we first used a PLS regression to identify weighted gene combinations with cortical expression maps that best matched maps of principal gradient differences between groups (PLS-1). 21 We then ran a series of enrichment analyses to examine diseases and functional processes that have been associated with identified gene combinations in previous genetics and functional genomics research.…”
Section: Discussionmentioning
confidence: 99%
“…In extratemporal epilepsy (ETE; middle row), a study focusing on children with frontal lobe seizures demonstrated that despite the absence of significant differences in structural network parameters in patients, structural modularity increased with more marked cognitive impairment (middle left) ( Vaessen et al, 2014 ) . When comparing fMRI activation patterns in a verbal working memory task, frontal lobe epilepsy patients showed targeted reductions in the recruitment of specific networks, notably fronto-parietal and dorsal attention systems, while effects in TLE patients were more widespread (middle right) ( Caciagli et al, 2022 ). As for idiopathic generalized epilepsy syndromes (IGE; bottom row), a study in patients with juvenile myoclonic epilepsy and their unaffected siblings investigated left hippocampal shape/positional anomalies and found associations to atypical activation during a verbal memory task (bottom left) ( Caciagli et al, 2019 ).…”
Section: Temporal Lobe Epilepsymentioning
confidence: 99%